Política, direitos e novos controles punitivos - Campello, Ricardo Urquizas (2013)
This work presents the emergency of new techniques of control and punishment exercised by the use of telematic monitoring, over the so-called criminals, according to the current demands for security. The equation liberty-security that is suffused by the effectuation of rights is also problematized. The research is situated in what Michel Foucault called neo-liberal governmentality and investigates the recent strategies of conducts conduction that extends the penal control to out of the bodies confinement spaces, without abdicating them. It is showed how the offenders tracking waters down the prison limits by its coupling to electronic modulations that formats jails without walls, mobile and flexible, in open environment. Punctual precedence of monitoring technologies in the United States is studied, as well as its transformations serving the current penal economy. Different punitive practices that nowadays are resized in electronic controls are presented. Eclectic discourses and the several political forces that bring about the offenders tracking are analysed. The implementation of the electronic monitoring of condemned and processed people by the penal system in Brazil is situated as a truth construction from the inextricable relation between legalisms and illegalisms. The questioning of the continuity of the punishment over bodies as a support of the politics that is today exercised and lengthened by means of new punitive controls anchored in the expansion of the double rights-security.